2014
DOI: 10.1530/eje-13-0609
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D levels and liver histological alterations in children with nonalcoholic fatty liver disease

Abstract: Objective: To investigate the association between plasma vitamin D (VD) levels and histological liver damage in children with nonalcoholic fatty liver disease (NAFLD). Subjects and methods: In this cross-sectional study, carried out in a tertiary care center for obesity, 73 consecutive overweight and obese children with persistently elevated serum aminotransferase levels and diffusely hyperechogenic liver on ultrasonography were selected for liver biopsy. Nonalcoholic steatohepatitis (NASH) and fibrosis were h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 103 publications
(87 citation statements)
references
References 31 publications
5
78
0
4
Order By: Relevance
“…Among studies that assessed the liver with a liver biopsy, 2 studies conducted on overweight and obese children and 1 study conducted on overweight adults found an inverse association between the level of 25-OH vitamin D and the severity of steatosis, inflammation, ballooning, and fibrosis (Manco et al, 2010;Nobili et al, 2014;Targher et al, 2007). By contrast, this association was not found in a recently published large cohort of obese patients (Bril et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Among studies that assessed the liver with a liver biopsy, 2 studies conducted on overweight and obese children and 1 study conducted on overweight adults found an inverse association between the level of 25-OH vitamin D and the severity of steatosis, inflammation, ballooning, and fibrosis (Manco et al, 2010;Nobili et al, 2014;Targher et al, 2007). By contrast, this association was not found in a recently published large cohort of obese patients (Bril et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies, involving patients with non-cirrhotic NAFLD, have suggested that low levels of serum 25-hydroxyvitamin D 3 are associated with a greater severity of NAFLD histology, independent of several potential confounders, including the features of MetS [16,[58][59][60][61]. Although it could be also hypothesized the existence of reverse causality between NAFLD and low serum 25-hydroxyvitamin D 3 levels, some experimental studies have shown that the liver expression of both CYP2R1 and CYP27A1 (i.e., two cytochromes implicated in the 25-hydroxylation of vitamin D 3 ) is preserved in patients with NASH or chronic hepatitis C virus [62].…”
Section: Low Bone Mineral Density (Osteoporosis/osteomalacia)mentioning
confidence: 99%
“…Vitamin D deficiency, defined as vitamin D 25-OH levels < 20ng/ml, was present in 50% of 64 children with NAFLD [51]. In a follow-up study of 73 overweight and obese Italian children with NAFLD, vitamin D 25-OH levels were significantly lower in those children with NASH than those without NASH [52]. In contrast, in a study of 102 children in the NASH CRN, although low vitamin D 25-OH levels were common there was no association with the histologic severity of disease [53].…”
Section: Introductionmentioning
confidence: 99%